Cytoplasmic Mg 2+ supersedes carbon source preference to dictate Salmonella metabolism - Nick D. Pokorzynski; Katarina A. Jones; Shawn R. Campagna; Eduardo A. Groisman (Proceedings of the National Academy of Sciences, 2025)
Glucose is the preferred carbon source of most studied microorganisms. However, we now report that glucose loses preferred status when the intracellular pathogen Salmonella enterica serovar Typhimurium experiences cytoplasmic magnesium (Mg 2+ ) starvation. We establish that this infection-relevant stress drastically reduces synthesis of cyclic adenosine monophosphate (cAMP), the allosteric activator of the cAMP receptor protein (CRP), master regulator of carbon utilization. The resulting reduction in cAMP concentration, which is independent of carbon source, decreases transcription of CRP-cAMP-activated carbon utilization genes, hinders carbon source uptake, and restricts metabolism, rendering wild-type bacteria phenotypically CRP − . A cAMP-independent allele of CRP overcame the transcriptional, uptake, and metabolic restrictions caused by cytoplasmic Mg 2+ starvation and significantly increased transcription of the glucose uptake gene when S. Typhimurium was inside murine macrophages. The reduced preference for glucose exhibited by S. Typhimurium inside macrophages reflects that transcription of the glucose uptake gene requires higher amounts of active CRP-cAMP than transcription of uptake genes for preferred carbon sources, such as gluconate and glycerol. By reducing CRP-cAMP activity, low cytoplasmic Mg 2+ alters carbon source preference, adjusting metabolism and growth.